The amino acid sequence of chicken histone F3 - Brandt, Wolf Friedrich (Department of Molecular and Cell Biology, 2016)
Histone F3 (III) from chicken erythrocytes was isolated by selective extraction from nucleoprotein with ethanolic-HCl and purified by a single gel filtration step. This protein was found to be homogeneous by the following criteria: gel filtration, electrophoretic mobility, N- and C-terminal amino acid residues and amino acid analysis. The primary structure of this histone was established without resorting to the use of overlapping sequences. This has been achieved with specific chemical cleavages rather than enzymatic degradations chosen and applied, first to the original protein chain, and subsequently to the generated polypeptides, to yield sets of not more than 3 peptides in any single cleavage. Their relative position in the protein or polypeptides became evident after comparison of the N- and C-terminal amino acids in the cleavage products and the uncleaved starting material. The simplicity of the peptide mixture after each cleavage, resulting in easy separation of the peptides, together with the highly efficient Edman degradation of automatic sequencing, allowed a rapid and relatively nonlaborious primary structure determination. Finally, the amino acid sequence is compared with those of protamines and other histones. The evolution and the structure of this protein in relation to DNA is briefly considered.